Pengaruh CR, ROE, dan DER Terhadap Nilai Perusahaan pada Perusahaan Food & Beverage - Gandi, Vinka Ameliya; Apriyanti, Christina; Kardinal, Kardinal (MDP Student Conference, 2025)
This study aims to assess the effect of CR, ROE, and DER on Firm Value (PBV) in Food and Beverage Sub-Sector Companies listed on the Indonesia Stock Exchange in 2019-2023. This study is quantitative. This study uses secondary data. The sample in this study consisted of 30 companies that met the requirements. This study applies purposive sampling as a sampling method. The findings of this study describe CR, ROE, and DER have a positive and significant effect on Firm Value (PBV). CR, ROE, and DER simultaneously affect Firm Value (PBV).